Review essay: Trans bodies, trans selves: A resource by and for transgender communities, edited by Laura Erickson-Schroth (2nd edition) - Tiffany Sostar (International Journal of Narrative Therapy and Community Work, 2024)
Tiffany Sostar reviews Trans bodies, trans selves: A resource by and for transgender communities, edited by Laura Erickson-Schroth (2022, 2nd edition). Oxford University Press. 728pp. ISBN 9780190092726.